The independence of Peru along the sea route - Grau Umlauff, Fernando (2022)
After the united provinces located in South America reached independence, it was clear that the biggest threat for their republic would come from the sea. Moreover, South America's independence would not be possible without the viceroyship of Peru becoming independent from Spain's rule. It was understood that defeating the Spanish rule throughthe highlands of Peru would mean failure and doing it along the sea was the way toachieve independence. This meant the control of the sea located in the southern part of the Pacific Ocean. The job was concluded, first with the landing in Paracas on the 7th of September and then with the proclamation of independence of Perú the 28th of July in1821.